Comparação dos resultados da gravidez molar entre adolescentes da América do Norte e da América do Sul - Soares, Renan Rocha [UNESP] (2016)
Although 10-34% of patients with molar pregnancy are adolescent, the influence of young age on the clinical presentation and risk of developing post-molar gestational trophoblastic neoplasia (GTN) is still unclear. Objectives. To compare complete hydatidiform mole (CHM) clinical presentation and risk factors associated with developing GTN between North American adolescents and South American counterparts. Methods. Non-concurrent cohort study including adolescents ( 20 years) with CHM referred to centers in North America (New England Trophoblastic Disease Center, Harvard University,USA) between 1973-2009, and South America (Botucatu Trophoblastic Disease Center-São Paulo State University-Unesp, Brazil; Trophoblastic Unit of Central University of Venezuela and Maternidad Concepcion Palacios of Caracas, Venezuela) between 1990-2009. Patient clinical data collected included age, gestational age at diagnosis, uterine size, pre-evacuation hCG, presence of theca lutein cysts, anemia, vaginal bleeding, preeclampsia, and hyperemesis. Study participants were allocated into two groups of adolescents: North American (NA,n=195) and South American (SA,n=231). Results. At presentation, anemia (SA=48% vs NA=15%;p<0.001), hyperemesis (SA=14% vs NA=6%;p=0.003), and elevated serum hCG (SA=229591 mUI/mL vs NA=14000 mUI/mL ; p<0.001) were more frequent in SA than in NA. In SA, preeclampsia (SA:OR=4.33(1.37-13.65) vs NA:OR=0.34(0.04- 2.86), uterine size>gestational age (SA:OR= 2.50(1.26-4.94) vs NA: OR=1.69(0.87- 3.26); and cysts > 6cm (SA: OR= 2.25(0.80-6.33) vs NA:OR=1.43(0.57-3.56) had greater impact on the risk of developing post-molar GTN. In contrast, only vaginal bleeding (SA:OR=1.37(0.64-2.91) vs NA: OR=2.79(1,10-7, 06) influenced GTN risk in NA. Conclusions. Compared to NA, CHM among SA adolescents showed medical complications more frequently, and clinical features with greater impact on risk of GTN development.